Liberalizing Basic Telecommunications : The Asian Experience - Fink, Carsten; Mattoo, Aaditya; Rathindran, Randeep (World Bank, Washington, DC, 2014)
The authors examine the liberalization of the basic telecommunications sector in Asian countries with a view to identifying good policy and determining how multilateral negotiations can promote it. They find that most Asian governments, despite the move away from traditional public monopolies, are still unwilling to allow unrestricted entry, eliminate limits on private and foreign ownership, and establish strong, independent regulators. But where comprehensive reform has been undertaken-including privatization, competition, and regulation-the availability of main lines, the quality of service, and the productivity of labor are significantly higher. Somewhat surprisingly, little unilateral liberalization has occurred since the last round of telecommunications negotiations under the General Agreement on Trade in Services (GATS). The new round therefore faces the challenge of not merely harvesting unilateral liberalization, as in the past, but of negotiating away existing restrictions. Since quantitative restrictions on the number of telecommunications service suppliers are pervasive, deepened GATS rules could help ensure transparent and nondiscriminatory allocation of licenses. There may also be a need to sharpen the regulatory principles established in the last round and to create rules that safeguard not only the rights of foreign suppliers but also those of consumers.